Discriminación a los estudiantes con necesidades educativas especiales - Almachi Oñate, Fátima de Jesús (2017)
The present research on discrimination of students with special educational needs was carried out in order to establish the factors of not associated with a disability and their influence on academic development. The research has taken as a study problem the influence of discrimination towards children with special educational needs for their cognitive development. The project had as beneficiaries the teachers, students and parents of the "Victor Manuel Garcés School in the Saquisilí Canton, Cotopaxi Province.The methodological design that has been applied in the development of research was framed in a quantitative approach Complemented by field research and documentary bibliographical research, which allowed the achievement of a descriptive level of the object of study. The research technique was applied through the instrument of the questionnaire addressed to the parents and teachers of the " Víctor Manuel Garcés " School, the objective of collecting their perceptions regarding the discrimination of students with Special educational needs in the institutions of regular education. The following results have been obtained: Parents have a negative attitude and rejection towards the Approach to the special educational needs of the teachers say that they know little about these strategies that can be undertaken for the educational approach of children with SEN not associated with a disability. In the same sense of the documents it is manifested that within the classroom they occur with the frequent discriminations between the students. Considering that discrimination represents an act of distinction and exclusion in the specific case of research occurs when a student presents some kind of special educational needs, these attitudes can generate affectations in the student that harm his emotional state and his predisposition into the Teaching learning process.